Pengaruh Keadilan Distributif Dan Prosedural Kompensasi Terhadap Kepuasan Kerja Dan Kinerja Paramedis Di Rumah Sakit - Atmojo, Singgih Tiwut; Tjahjono, Heru Kurnianto (Jurnal Bisnis Teori & Implementasi)
This study discusses the organizational justice include distributive justice compensation and procedural justice compensation to employees performance both directly and indirectly influenced by job satisfaction. The populations in this study were all para-medic employees in RSJ Prof. Dr. Soerojo Magelang totaling 142 people. Data were collected by survey method is to provide a list of questions or questionnaires directly to the respondent. Data analysis techniques in this study using analysis of SEM (Structural Equation Modeling) program operated by AMOS 21. The results showed that distributive justice compensation significant positive effect on job satisfaction; procedural justice compensation significant positive effect on job satisfaction; distributive justice compensation are not significantly to employees performance; procedural justice compensation are not significantly to employees performance; job satisfaction significant positive effect on employees performance; job satisfactions as a mediating influence of distributive justice compensation and procedural justice compensation to employees performance.